Evaluasi Bangunan Ruko Sebagai Sebuah Langkah Penghematan Energi (Studi Kasus : Ruko Real Estate di Beurawe Kota Banda Aceh) - Siti Zulfa Yuzni; Mirza Mahmud; Irin Caisarina; Riza Priandi (Jurnal RAUT, 2022)
Elvasko Real Estate Ruko is one of the shophouses in Beurawe which is located on Jalan Jeumpa Beurawe, Kuta Alam District, Banda Aceh City. The city of Banda Aceh is a tropical region with temperatures ranging from 25.5C to 32.5C. This has an impact on the high consumption of electrical energy as a result of the use of artificial ventilation in buildings to increase comfort in the room. The purpose of the study was to evaluate the effect of the facade on the shophouse building on the acquisition of the OTTV value or Overall Thermal Transfer Value as an energy-saving measure. This study also identifies the possibility of utilizing solar panels to save energy use. This research method is a quantitative study with an approach to calculating the OTTV value for each area of the outer wall of the building and calculating the need for solar panels, and simulating solar shading with Ecotect software. The results showed that the OTTV calculation results in the shophouse building were 34.13 W/m2; this still met the overall thermal transfer value limit on the outer or inner walls of the building based on SNI 03-6389-2011. The possibility of using solar panels for energy saving is by installing solar panels with a capacity of 100 wp (Watt Peak). This study calculates the use of 112.5 solar panels with a need of 3,750 Ampere of battery to install in the shophouse. The front shop faces the west. It can contribute to the more heat absorbed. Ecotec simulation conducted in this study shows that the front facade of the building is exposed to direct sunlight from 14:00 to 18:00 WIB. Therefore, the shadings are recommended to install on this side.